Pan-Islamic international cooperation and anticolonialism: South Asia, Turkey, and Southeast Asia - Islam, Arshad (2019)
Non-Western cultures and peoples, such as the Islamic, Hindu, Confucian, and Orthodox Christian, have been systematically oppressed, colonized, and dominated by the ideology, arms, and economies of the West for over two centuries under the imperialist ‘clash of civilizations’. Numerous techniques have been adopted by the oppressed peoples of Asia, Africa, and Latin America to resist this domination, and to promote peace, harmony, and stability. One of these strategies that was manifest during the anticolonial movement in South Asia, Turkey, and Southeast Asia was pan-Islamism, which was relatively forgotten by history until Turkey more recently began to assume its historic role as a leading civilization in Asia and the wider Muslim world. Most modern development literature is premised on the assumption that Western civilization is the model to which all developing nations must aspire, and assistance in economic development is generally premised on accepting a raft of Western neo-imperialist demands that may be contrary to Asian and African cultural mores. In response to this, nationalist movements have become increasingly skeptical about the international development agenda, and Eurasian countries such as Russia, Turkey, Pakistan, India, and China are increasingly rejecting subservience to the political and cultural demands of the West. This paper explores examples of the role of pan-Islamism in resisting European colonialism. It particularly analyses the role of Indian Muslims in assisting the Ottoman Caliphate (e.g. financing the Hejaz Railway and supporting the Turkish cause during the Balkan Wars), the role of the Ottomans in Sumatran resistance to Dutch colonialism, and the resumption of pan-Islamic ties manifest in modern Turkish disaster relief efforts in Indonesia. It concludes that pan-Islamism is already a powerful force in international development. It shows that the pan-Islamic platform offers great scope for developing countries to autonomously assist each other without the shackles of the neo-imperialist agendas, recovering their historical position and dignity as vibrant, compassionate societies.